2014
DOI: 10.1186/2045-7022-4-8
|View full text |Cite
|
Sign up to set email alerts
|

Markers of gut mucosal inflammation and cow's milk specific immunoglobulins in non‐IgE cow's milk allergy

Abstract: BackgroundAllergy to cow’s milk protein (CMP) may cause gastrointestinal (GI) symptoms in the absence of CMP specific IgE. The immunological mechanisms involved in such disease are not fully understood. Therefore we examined markers of gut mucosal inflammation and the immunoglobulin profiles in children with Gl symptoms suspected of cow’s milk protein allergy (CMPA).Patients and methodsWe prospectively recruited infants and young children (n = 57; median age 8.7 months) with gastrointestinal complaints suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 36 publications
1
35
2
Order By: Relevance
“…Increased gut permeability and intestinal inflammation with impaired immune-regulatory mechanisms have been shown in children with allergic disease 55 , and also in children with type 1 diabetes 56 . Consistent with reports of dysbiosis in children with allergic manifestations, an aberrant gut microbiome has been associated with type 1 diabetes 57,58 .…”
Section: An Aberrant Gut Microbiome In Early and Late Onset Ncdsmentioning
confidence: 99%
“…Increased gut permeability and intestinal inflammation with impaired immune-regulatory mechanisms have been shown in children with allergic disease 55 , and also in children with type 1 diabetes 56 . Consistent with reports of dysbiosis in children with allergic manifestations, an aberrant gut microbiome has been associated with type 1 diabetes 57,58 .…”
Section: An Aberrant Gut Microbiome In Early and Late Onset Ncdsmentioning
confidence: 99%
“…[10][11][12] Fecal calprotectin is a potentially important clinical test as a marker of gastrointestinal tract inflammation and has been increasingly used as a non-invasive marker for the diagnosis of bowel inflammation or gastrointestinal allergic diseases. 10,11,13 Although many studies have reported the relationship between fecal calprotectin and gastrointestinal inflammation or allergic diseases, calprotectin has rarely been studied in AD. The aims of this study were to examine fecal calprotectin levels in children with AD and to investigate its relationship with the severity of AD.…”
Section: Discussionmentioning
confidence: 99%
“…4 Numerous investigators have shown that changes in the gut microbiota and intestinal inflammation have been associated with the development of allergic diseases. 6,8,13,23 The gut microbiota controls intestinal inflammation, which further modulates the development of the systemic immune system. 8,23 Altered gut microbiota induces epithelial damage resulting in increased intestinal inflammation, altered gut permeability and immunological balance, which affect the development of allergic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased gut permeability and intestinal inflammation with impaired immune-regulatory mechanisms have been shown in children with allergic disease 55 , and also in children with type 1 diabetes 56 . Consistent with reports of dysbiosis in children with allergic manifestations, an aberrant gut microbiome has been associated with type 1 diabetes 57, 58 .…”
Section: An Aberrant Gut Microbiome In Early and Late Onset Ncdsmentioning
confidence: 99%